Middle third clavicle fractures are the most common fractures in head injuries: a biomechanical and epidemiological study in 1000 patients - Rajagopalan, Sridhar Gopal; Vasudevan, Saravanan; Veeraraghavan, Raghav Ravi; Vanchi, Pravin Kumar; Murugesan, Mohan Kumar (International Journal of Research in Orthopaedics, 2020)
A consecutive series of 1000 cases of head injury, out of which 385 patients presented with fractures. In the 385 patients with fractures, 179 patients presented with clavicle fractures, among that, 127 are middle third fractures. Out of the 189 patients who had clavicle fractures, 90% of them had direct blow to shoulders and 10% had fallen on the outstretched hand. This variation with the mechanism of injury was further investigated by biomechanical analysis of the forces involved in clavicular fractures.